Bioadsorption and enzymatic biodecolorization of effluents from ethanol production plants. (March 2020) - Ziaei-Rad, Zhila; Nickpour, Mojdeh; Adl, Mehrdad; Pazouki, Mohammad
Abstract: Distillery effluent must be handled in compliance with the demands and obligations of Environmental Quality Standards (EQS). As Iranian bioethanol plants often face the problem of high color content, therefore, an efficient decolorization process is required to determine the quality of effluent so as to meet demanded standards. The existing color in effluent is identified as Melanoidins, which is adsorbed by fungal mycelia or biodegraded. In this work, the biodecolorization mechanism was studied using Aspergillus fumigatus UB2 60. A color removal rate of 47% was obtained at an incubation time of 96 h at 30 °C. FTIR spectrum proved the presence of Melanoidins. SEM micrographs showed the accumulation of specified pigments in the mycelia. The release of color from fungal mycelia to 0.5 N NaOH proved the color adsorption on the surface of mycelia. Poly-acrylamide gel electrophoresis analysis (SDS/PAGE) proved that the presence of protein molecules in bio-decolorization culture. There was no existence of a trace amount of protein in the raw distillery wastewater. The decolorization was perceived as of dual mechanism.